GST : Positive and Negative Effects on Common Man in India - Kumar, Vikas (Journal of Commerce and Trade, 2016)
The Goods and Services Tax is considered as a biggest tax reform since 1947. It seeks to stream line the taxation system so that there is a single tax paid for supply of goods and services. The bill will replace nearly 15 states and federal taxes which is inline with the government focus on cooperative federalism and a mission for unity of Indian economy. The government want to implement GST on 1st April, 2017 and for this efforts are made continuously. The main expectation is that this land mark will go a long way in facilitating ease going business and enabling India to compete with World Trade. GST bill have a far reaching impact on all almost all the aspects in the business organization in the country for example pricing of products and services, supply chain optimization, IT, accounting and tax compliance system. That's why GST bill has been described as a reform measure of unparalleled importance in independent India. The GST bill facilitate "Make In India" by bringing India on single tax platform. It can be said that the real success of GST depends upon the impact on the common Indian consumer. The essence of GST is that all goods and services be taxed at moderate rate. Single tax for one India proves to be a game changer in a positive way and proves to be beneficial not only to the common man, but to the country as a whole.